RESEARCH AND ANALYSIS OF DRIED KISHMISH AND RAISINS FROM GRAPES OF SOUTH KAZAKHSTAN - M.T. Tokhanov,; Kantureyeva G.O.,; Lomolino G,; Urazbayeva K.A. ,; Taspolatova A.M,; Nurseitova Z.T, (Academic Scientific Journal of Chemistry, 2020)
Dried fruits, including raisins, are of particular interest in nutritional studies due to its unique chemical composition and natural qualities, which make raisins an attractive source of nutrients. Research and analysis of kishmish and dried raisins was performed in the department "Food Engineering" of M. Auezov SKSU. Dried fruits were prepared by scientifically justified and developed technology of drying fruits to obtain domestic environmentally friendly dried grapes by infrared irradiation after pre-treatment of raw materials without the use of chemical reagents. From this study, it can be concluded that the kishmish and raisins obtained from grapes varieties “Kishmish black”, “Bulls-eye”, grown in South Kazakhstan region contain sufficient amount of sucrose (5.17 and 4.75 respectively). Given samples also show high contents ofpotassium (17.98 and 33.02 respectively), calcium (1.19 and 2.07 respectively), phosphorus (1.41and 4.47 respectively), but iron contents is much less (0.21and 0.27 respectively) than usually. Consumers and stakeholdersmay get benefits by production and realization of suggested kishmish and raisins as regional brands of Kazakhstan or products with geographical indications (GI). In the future it is necessary to carry out a lot of work on branding the products offered by the authors, provided that it will satisfy the following values, such as technological novelty, rarity and uniqueness of the product, environmental friendliness of the manufacture and use of the product